Deletion of the adenosine A 2A receptor increases the survival rate in a mice model of polymicrobial sepsis - Meriño, Miguel; San Martín, Sebastián; Sandaña, Pedro; Herlitz, Kurt; Aguayo, Claudio; Godoy, Alejandro; Torres-Vergara, Pablo Torres-Vergara; Gonzalez, Marcelo; Troncoso, Felipe; Acurio, Jesenia; Escudero, Carlos
We aim to investigate the role of A2A receptor in peritonitis-related sepsis by injection of a fecal solution (FS) as a model of polymicrobial infection. C57/black J6 wild-type (WT) and A2A-deficient mice (A2AKO) were exposed to sepsis induced by intraperitoneal injection of a FS (FS-induced peritonitis) or instead was injected with saline buffer (Sham). Survival rate and sepsis score were measured up to 48 h. The presence of bacteria in tissue homogenates was analyzed. Telemetry and speckle laser Doppler were used for systemic blood pressure and peripheral blood perfusion analysis, respectively. Histological analysis and identification of active caspase 3 were performed in selected organs, including the liver. The survival rate of A2AKO mice exposed to FS-induced peritonitis was significantly higher, and the sepsis score was lower than their respective WT counterpart. Injection of FS increases (50 to 150 folds) the number of colonies forming units in the liver, kidney, blood, and lung in WT mice, while these effects were significantly attenuated in A2AKO mice exposed to FS-induced peritonitis. A significant reduction in both systolic and diastolic blood pressure, as well as in the peripheral perfusion was observed in WT and A2AKO mice exposed to FS-induced peritonitis. Although, these last effects were significantly attenuated in A2AKO mice. Histological analysis showed a large perivascular infiltration of polymorphonuclear in the liver of WT and A2AKO mice exposed to FS-induced peritonitis, but again, this effect was attenuated in A2AKO mice. Finally, high expression of active caspase 3 was found only in the liver of WT mice exposed to FS-induced peritonitis. The absence of the A2A receptor increases the survival rate in mice exposed to polymicrobial sepsis. This outcome was associated with both hemodynamic compensation and enhanced anti-bacterial response.